Macroeconomic determinants of stock market behaviour in South Africa - Junkin, Kyle (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2012)
This study investigates whether stock prices in South Africa are influenced by macroeconomic variables, and furthermore, the effects of financial crises on stock prices. The relationship between stock prices and the macroeconomy is a particularly important issue for investors, since a thorough understanding of such a relationship is likely to yield profitable or risk mitigating opportunities. Using monthly data for the period 1995 to 2010 the study focused at a macro level using the FTSE/JSE All Share Index, and at a micro level using sector indices. These included the construction and materials, financial, food producers', general retailers, industrial, mining and pharmaceuticals indices. The Johansen and Juselius (1990) multivariate cointegration approach was employed, along with impulse response and variance decomposition tests to address the issue. The results showed that macroeconomic variables do have a significant influence on stock prices in South Africa. Also, the influences of these variables were found to have an inconsistent effect across the sectors under investigation. For example, inflation was found to negatively influence the All Share Index, but impacted the industrial index positively. These inconsistent influences on the various sectors were seen to have important diversification implications for investors. The impact of past financial crises proved to be significant on certain indices, however, indices such as that of the pharmaceuticals sector was found to be largely unaffected by such crises. The findings of the study were discussed through an investor's perspective, and recommendations on investment decisions were given. The limitations of the study were such that certain results may have been influenced by a mis-specification of variables, particularly the Treasury bill rate.
Keywords: Stocks -- Prices -- South Africa; Macroeconomics; Risk management -- South Africa; Stock exchanges -- South Africa; Interest rates -- South Africa